Central regulation of motor cortex neuronal responses to forelimb nerve inputs during precision walking in the cat - Marple-Horvat, D E (Blackwell Science Inc, 1999)
1. The responses of neurones in forelimb motor cortex to impulse volleys evoked by single pulse electrical stimulation (at 1.5 or 2 times the threshold for most excitable nerve fibres) of the superficial radial (SR) and ulnar (UL) nerves of the contralateral forelimb were studied in awake cats both resting quietly and walking on a horizontal ladder. Nerve volley amplitude was monitored by recording the compound action potential elicited by the stimulus. 2. In the resting animal 34/82 (41 %) cells yielded statistically significant responses to SR stimulation, and 20/72 (28 %) responded to UL stimulation. Some responses were confined to or began with an increase in firing probability (‘excitatory’ responses) and others with a decrease in firing (‘inhibitory’ responses), typically including a brief interruption of the spike train (zero rate). Cells responding to both nerves usually yielded responses similar in type. Most (78 %) response onset latencies were less than 30 ms. Responses involved the addition or subtraction of from 3.4 to 0.1 impulses stimulus(−1) (most < 1 impulse stimulus(−1)). The distribution of response sizes was continuous down to the smallest values, i.e. there was no ‘gap’ which would represent a clear separation into ‘responsive’ and ‘unresponsive’ categories. Responses were commonest in the lateral part of the pericruciate cortex, and commoner among pyramidal tract neurones (PTNs) than non-PTNs. 3. During ladder walking most cells generated a rhythmic step-related discharge; in assessing the size of responses to nerve stimulation (20 studied, from 13 cells) this activity was first subtracted. Response onset latencies (90 % < 30 ms) and durations showed little or no change. Although most cells were overall more active than during rest both ‘excitatory’ and ‘inhibitory’ responses in both PTNs and non-PTNs were often markedly reduced in large parts of the step cycle; over some (usually brief) parts responses approached or exceeded their size during rest, i.e. response size was step phase dependent. Such variations occurred without parallel change in the nerve compound action potential, nor were they correlated with the level of background firing at the time that the response was evoked. When responses to both nerves were studied in the same neurone they differed in their patterns of phase dependence. 4. The findings are interpreted as evidence for central mechanisms that, during ‘skilled’, cortically controlled walking, powerfully regulate the excitability of the somatic afferent paths from forelimb mechanoreceptors (including low threshold cutaneous receptors) to motor cortex. Retention (or enhancement) of responsiveness often occurred (especially for ulnar nerve) around footfall, perhaps reflecting a behavioural requirement for sensory input signalling the quality of the contact established with the restricted surface available for support.